The rise of information activism: how to bridge dualisms and reconceptualise political participation. Issue 10 (2nd October 2016) - Halupka, Max
ABSTRACT: While conventional wisdom sees politics as involving collective action in the political arena, some contemporary approaches focus on connective action beyond the political arena. Crucially, both treat the distinction between arena and process definitions of politics, and relatedly between collective and connective, as dualisms. This paper looks to reconceptualise political participation by arguing that these two dualisms should be treated as dualities. In doing so, it posits a new form of political participation, 'information activism' and explores it in practice by drawing on survey data from the 2013 political protests in Turkey.